Innovation regional factors as part of the european economic system 2000 - 2010 - Verástegui Huanca, Lucio Leo (2018)
This working paper studies the factors of the Regional Innovation System in Europe in the period of 2000 – 2010 through an innovative methodology and based on a solid theory and empirical work. Innovation within a national economy is crucial to economic development and competitiveness both for the government as well as firms. Therefore, evolutionary theory has built the basis of innovation as an interactive system based on the synergy of various components that are involved and determine the innovative effort of each system. Finally, it delineates the components of the Regional Innovation System from 191 European regions through Factor Analysis, based on recompilation, treatment, and exhaustive analysis of indexes related to innovation. This working paper can serve as a starting point for future analysis of efficiency, potential improvement or simply generating effective public policies.